2017
DOI: 10.1039/c7ra08247a
|View full text |Cite
|
Sign up to set email alerts
|

Helical graphite metamaterials for intense and locally controllable magnetic fields

Abstract: We propose a novel class of bulk metamaterials, termed helical graphite (HG), which is able to produce intense magnetic fields under an external electrical bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…According to Porsev’s nomenclature with our slight modification of variables, concentrically expanded and extended carbohelicene and its analogues can be expressed as [ k , m ]­[ n ]­helicene, where k , m , and n represent the shaft radium, the width of the spiral ribbon, and the number of benzene rings, respectively (Figure a). There are several developments and mainstreams in helicene chemistry as shown in Figure a: (1) elongating the helicene in the helical direction with increasing the n number in classical all- ortho -fused [1,1]­[ n ]­helicenes (or simply [ n ]­helicene), (2) incorporating multiple helicene moieties to PAH for the synthesis of double, triple, quadruple, quintuple, and sextuple helicenes and those macrocycles, (3) embedding heteroatoms such as nitrogen and boron into helicene or substitution of benzene rings with nonhexagonal (hetero) aromatics such as furan, pyrrole, thiophene, and azulene, (4) extending the π-system in a peripheral direction (increasing m ) for the synthesis of laterally extended helicenes as represented by hexa- cata -hexabenzo­[7]­helicene and peri -perbenzo­[9]­helicene, (5) increasing the size of helicene pore/diameter (increasing k ) by the alternation of linear and angular ring fusion of hexagonal/nonhexagonal (hetero)­aromatics, so-called expanded helicenes. Among these, the development of expanded carbohelicenes has lagged due to the synthetic difficulty. They are expected to exhibit molecular encapsulation ability by taking advantage of their vacancies and novel electrical, optical, and chiroptical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Porsev’s nomenclature with our slight modification of variables, concentrically expanded and extended carbohelicene and its analogues can be expressed as [ k , m ]­[ n ]­helicene, where k , m , and n represent the shaft radium, the width of the spiral ribbon, and the number of benzene rings, respectively (Figure a). There are several developments and mainstreams in helicene chemistry as shown in Figure a: (1) elongating the helicene in the helical direction with increasing the n number in classical all- ortho -fused [1,1]­[ n ]­helicenes (or simply [ n ]­helicene), (2) incorporating multiple helicene moieties to PAH for the synthesis of double, triple, quadruple, quintuple, and sextuple helicenes and those macrocycles, (3) embedding heteroatoms such as nitrogen and boron into helicene or substitution of benzene rings with nonhexagonal (hetero) aromatics such as furan, pyrrole, thiophene, and azulene, (4) extending the π-system in a peripheral direction (increasing m ) for the synthesis of laterally extended helicenes as represented by hexa- cata -hexabenzo­[7]­helicene and peri -perbenzo­[9]­helicene, (5) increasing the size of helicene pore/diameter (increasing k ) by the alternation of linear and angular ring fusion of hexagonal/nonhexagonal (hetero)­aromatics, so-called expanded helicenes. Among these, the development of expanded carbohelicenes has lagged due to the synthetic difficulty. They are expected to exhibit molecular encapsulation ability by taking advantage of their vacancies and novel electrical, optical, and chiroptical properties.…”
Section: Introductionmentioning
confidence: 99%
“…They are expected to exhibit molecular encapsulation ability by taking advantage of their vacancies and novel electrical, optical, and chiroptical properties. Particularly, charge carrier mobilities and nanospring properties ,, have received a lot of attention, and computational studies have been conducted . Despite the development of various expanded helicenes containing nonhexagonal ring structures, such as heliphen and expanded helicenes containing heteroatoms, –i there are fewer reports on the synthesis of expanded helicene consisting of all-benzene rings as a helicene core. , …”
Section: Introductionmentioning
confidence: 99%
“…We hope that these results pave the way for a more realistic design of the nanosolenoids. To the best of our knowledge, this is the first study of the finite-length nanosolenoid where the fringe effects were not ignored. It is shown that the magnetic fields of the finite nanosolenoids can be an order of magnitude smaller than the field of infinite ones, and spatial distribution of fields is more complex.…”
Section: Introductionmentioning
confidence: 94%
“…An electromagnetic conversion in the solenoid in a form of the helical graphene nanostructures joined in a single layer wound around a dislocation line was suggested and theoretically studied, too . As examples of pure carbon-based materials, one can also cite the nanometer-sized graphite helical structures, which behave as a collection of individual, closely packed nanosolenoids, some graphene spiral structures, and the various helically coiled nanotubes with very complex structures. , The large magnetic fields are anticipated to be realized using solenoids with the carbon nanotubes-copper composite materials . Finally, our previous calculations show that much more efficient nanosolenoids are possible if one turns from carbon to the chiral gold nanotubes (AuNTs) .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation